Systematic Literature Review: Correlated Fuzzy Logic Rules for Node Behavior Detection in Wireless Sensor Network - Shahidah, Noor; Azni, A. H; Mohd Alwi, Najwa Hayaati; Seman, Kamatuzzaman; Bakar, Noor Hasrina (Journal of Telecommunication, Electronic and Computer Engineering (JTEC), 2017)
In distributed wireless sensor network, the possibility for one or several nodes to become faulty is directly proportional upon the number of nodes within the network. Unnecessary control of the network triggers the anomaly, faulty and misbehavior in nodes which anyhow yield to degradation of network performance. Therefore, the identification of node behavior in distributed sensory system is crucially important to improve the network performance throughout the monitoring period. Though the detection schemes are several, Fuzzy logic for node behavior detection in WSN however present a more accurate incentive as it considered the uncertainties inherited in the WSN environment during the fault diagnosis period. This paper analyzes several fuzzy logic approaches for correlated node behavior detection. With six primary articles, this paper provides systematic literature review (SLR) and presents an overview of current design of research trend in this area.